Ginsenoside Rb1 alleviates renal tubular epithelial cell injury in diabetic kidney disease by inhibiting the aldose reductase activity - Wang Meng-jing; Luo Yi; Liu Shu-fen; Yuan Shuang; Huang Hao (Linchuang shenzangbing zazhi, 2025)
ObjectiveTo investigate the protective effect of ginsenoside Rb1 on renal tubular epithelial cell injury in diabetic kidney disease and its mechanism.MethodsPrimary human renal cortical proximal tubular epithelial cells （HK-2） were cultured in vitro. HK-2 cells were divided into the control group， control ＋ ginsenoside Rb1 （10 μmol/L） group， high glucose （30 mmol/L） group， high glucose （30 mmol/L） ＋ ginsenoside Rb1 （10 μmol/L） group， and high glucose （30 mmol/L） ＋ epalrestat （100 μmol/L） group. db/m and db/db mice at 16 weeks of age were randomly divided into the db/m group， db/m ＋ ginsenoside Rb1 （40 mg/kg oral gavage） group， db/db group， and db/db ＋ ginsenoside Rb1 （40 mg/kg oral gavage） group. Western blotting was used to detect expression levels of the apoptosis-related proteins ［B-cell lymphoma-2 （Bcl-2）， Bcl-2-associated X protein （Bax）， and cleaved caspase-3］， oxidative stress-related proteins ［caspase 9， cytochrome complex （Cyt C）， and NADPH oxidase 4 （NOX4）］， and aldose reductase （AR）. Flow cytometry was used to observe the apoptotic rate of HK-2 cells. Reactive oxygen species （ROS） and Mitochondrial Superoxide Indicator （MitoSOX） fluorescence staining were used to detect the oxidative stress level of HK-2 cells. The binding ability of ginsenoside Rb1 to AR was detected by molecular docking. The changes in renal tubular mesangium were observed by PAS staining.ResultsIn comparison to the control group， protein level of Bcl-2 （0.37±0.12 vs 1.16±0.10） was significantly lower， while those of Bax （2.18±0.08 vs 1.16±0.03）， cleaved caspase 3 （2.17±0.09 vs 1.14±0.02）， caspase 9 （2.16±0.08 vs 1.20±0.03）， Cyt C （1.98±0.09 vs 1.13±0.06） and NOX4 （2.15±0.11 vs 1.20±0.07） were significantly higher in the high glucose group （P<0.001）. In comparison to the high glucose group， protein level of Bcl-2 （0.62±0.30 vs 0.37±0.12） was significantly higher， while those of Bax （0.73±0.08 vs 2.18±0.08）， cleaved caspase 3 （0.68±0.10 vs 2.17±0.09）， caspase 9 （1.62±0.12 vs 2.16±0.08）， Cyt C （1.59±0.10 vs 1.98±0.09） and NOX4 （1.52±0.08 vs 2.15±0.11） were significantly lower in the high glucose ＋ ginsenoside Rb1 group （P<0.01）. In comparison to the control group， ROS （43.85±3.25 vs 25.06±2.68） and MitoSOX levels （60.08±2.32 vs 22.50±0.68） were significantly higher in the high glucose group （P<0.001）. In comparison to the high glucose group， ROS （30.15±3.52 vs 43.85±3.25） and MitoSOX levels （32.06±1.89 vs 60.08±2.32） were significantly lower in the high glucose ＋ ginsenoside Rb1 group （P<0.01）. Molecular docking showed that ginsenoside Rb1 could stably bind to AR protein. Compared with the high glucose group， MitoSOX level was both significantly reduced in the high glucose ＋ ginsenoside Rb1 group （21.08±2.48 vs 44.85±2.08） and high glucose ＋ epalrestat group （23.62±2.28 vs 44.85±2.08）， showing a similar outcome （P<0.01）. Compared with the db/db group， mice in the db/db ＋ ginsenoside Rb1 group had significantly lower body weight ［（41.49±2.54） g vs （46.80±5.16） g］， blood sugar ［（26.98±3.53） mmol/L vs （30.22±3.49） mmol/L］ and urine albumin-creatinine ratio ［（8.43±3.31） mg/g vs （11.40±2.20） mg/g］ （P<0.001）. Compared with the db/m group， mice in the db/db group showed obvious glycogen deposition in renal tubules， mesangial matrix expansion， and higher mesangial area fraction （0.67±0.10 vs 0.24±0.05） （P<0.001）. Compared with the db/db group， mice in the db/db ＋ ginsenoside Rb1 group presented significantly alleviated glycogen deposition and mesangial matrix expansion in the renal tubules， with a significantly lower mesangial area fraction （0.36±0.04 vs 0.67±0.10） （P<0.01）.ConclusionGinsenoside Rb1 can bind to AR and inhibit its activity to reduce renal tubular epithelial cell injury in high glucose environment.